Consumer disputes and consumer dispute resolution in Japan - Karaiskos, Antonios (Penerbit Universiti Kebangsaan Malaysia, 2017)
This article examines the consumer dispute resolution system, as well as some representative consumer disputes in Japan. In Japan, it can be said that the major three actors of the consumer dispute resolution system are public authorities pursuing consumer interests, bodies offering alternative dispute settlement for consumers and consumer organizations engaging in consumer protection activities. In this article, the structure and issues of each of these actors is analyzed. Then, the author provides an overview of some major categories of consumer disputes, which shed light to the tendencies and problems in the field of consumer law in Japan. The author reaches the conclusion that the legislation in force seems to be insufficient for ensuring a proper level of consumer protection, and that future reforms, as well as innovative activities by local authorities are to be counted on. Further, a deep reconstruction of the social phenomena giving birth to such disputes, as well as a shift from a “consumer protection versus business interests” mentality to a “consumer protection and/plus business protection” model seems to be indispensable.